Potential of Black Rice Mutants (M4) Through Genetic Parameters to Develop Superior Drought-Resistant Varieties - Irmayani, Irmayani; Fauzi, Taufik; Sudharmawan, A. A. Ketut; Mulyati, Mulyati; Suwardji, Suwardji (Jurnal Biologi Tropis, 2024)
Rice plays an important role in meeting carbohydrate requirement and calorie needs to ensure food security. However, in recent years, rice productivity has decreased due to land conversion and climate change such as El Niño. The productivity of drought-resistant rice can be increased through breeding. Genetic diversity and heritability are important genetic parameters in the plant breeding process. Information about genetic diversity and heritability helps determine genetic progress through selection. This research aims to examine the potential genetic diversity and heritability of several mutant lines (M4) of black rice (G10) in order to develop superior rice varieties that are adaptive to dry land. In this research, we used experimental methods using a Randomized Block Design (RBD), calculating the value of the Genetic Diversity Coefficient (GDC) and heritability between quantitative characters. The results of narrow genetic research were found in the characteristics of the number of productive tillers and weight of 100 grains, while high heritability was found in the characters of plant height, moderate heritability was found in the total number of tillers, panicle length, number of empty grains per panicle, and weight of 100 grains. Overall, this research succeeded in identifying mutant lines (M4) of black rice (G10) which have the potential to be developed into superior varieties, especially for cultivation in dry land.